Minor differences in body condition and immune status between avian influenza virus‐infected and noninfected mallards: a sign of coevolution?. Issue 2 (31st December 2014) - van Dijk, Jacintha G. B.; Fouchier, Ron A. M.; Klaassen, Marcel; Matson, Kevin D.
Abstract Wildlife pathogens can alter host fitness. Low pathogenic avian influenza virus (LPAIV) infection is thought to have negligible impacts on wild birds; however, effects of infection in free‐living birds are largely unstudied. We investigated the extent to which LPAIV infection and shedding were associated with body condition and immune status in free‐living mallards (Anas platyrhynchos), a partially migratory key LPAIV host species. We sampled mallards throughout the species' annual autumn LPAIV infection peak, and we classified individuals according to age, sex, and migratory strategy (based on stable hydrogen isotope analysis) when analyzing data on body mass and five indices of immune status. Body mass was similar for LPAIV‐infected and noninfected birds. The degree of virus shedding from the cloaca and oropharynx was not associated with body mass. LPAIV infection and shedding were not associated with natural antibody (NAbs) and complement titers (first lines of defense against infections), concentrations of the acute phase protein haptoglobin (Hp), ratios of heterophils to lymphocytes (H:L ratio), and avian influenza virus (AIV)‐specific antibody concentrations. NAbs titers were higher in LPAIV‐infected males and local (i.e., short distance) migrants than in infected females and distant (i.e., long distance) migrants. Hp concentrations were higher in LPAIV‐infected juveniles and females compared to infected adults and males. NAbs, complement, and Hp levels were lower in LPAIV‐infected mallards in early autumn. Our study demonstrates weak associations between infection with and shedding of LPAIV and the body condition and immune status of free‐living mallards. These results may support the role of mallards as asymptomatic carriers of LPAIV and raise questions about possible coevolution between virus and host.